Spatial spillover of fintech innovation on green economic growth based on 30 provinces in China - Ma, Haoyuan; Zhou, Yunzhu; Pan, Yuhan; Dong, Rui; Tang, Decai (Frontiers in Environmental Science, 2025)
In the context of global concerns about climate change and environmental pollution, green economy is a key path to sustainable development. This study focuses on the impact of FinTech (FI) on China’s green economic growth (GEG) and regional differences to support green economic development. The panel data of 30 provinces in China from 2011 to 2021 are selected to analyse the relationship between fintech innovation and green economic growth with the help of spatial Durbin model, and spatial factors are taken into account to ensure that the study is scientific and reliable. Fintech innovation significantly promotes green economic growth, with positive spatial spillover effects. However, there are obvious regional differences, as the eastern part of China has developed its economy and financial technology, and its financial technology promotes green economic growth much more than that of the central and western parts of China, showing a transitional situation between the east and the west, and the central part of China. Fintech promotes China’s green economic growth, but regional development is uneven. While the eastern part of the country makes good use of fintech, the central and western parts of the country need to improve financial infrastructure and cultivate talents. This study provides empirical evidence on the development of green economy in Chinese cities, which will help coordinate the development of science and technology with economic development, formulate differentiated policies, and contribute Chinese experience to global green development.